2005
DOI: 10.1002/mds.20750
|View full text |Cite
|
Sign up to set email alerts
|

The Parkinson–Control study: A 1‐year randomized, double‐blind trial comparing piribedil (150 mg/day) with bromocriptine (25 mg/day) in early combination with levodopa in Parkinson's disease

Abstract: Dopamine agonists have been recommended as early treatment for Parkinson's disease (PD), alone or combined with levodopa. Piribedil is a non-ergot selective D(2)/D(3) agonist with alpha(2) antagonist properties shown to be effective in the treatment of PD. This 12-month international, randomized, double-blind trial aimed to assess the efficacy of piribedil 150 mg versus bromocriptine 25 mg, in early combination with levodopa in Stage I to III PD patients. Motor efficacy was assessed using the Unified Parkinson… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
1
5

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(35 citation statements)
references
References 30 publications
1
28
1
5
Order By: Relevance
“…The present controlled study reinforces this treatment strategy with piribedil, another dopamine agonist. Although not marketed in several countries, piribedil was chosen in this study because of its broad use in France over several decades with well known safety profile and relatively low cost compared with more recent dopamine agonists, the fact that it is a non-ergot drug, its known efficacy on motor symptoms in Parkinson's disease but also based on early studies indicating a benefit on depression (Post et al, 1978;Castro-Caldas et al, 2006;Rascol et al, 2006Rascol et al, , 2010. Most importantly, in a previous study (Thobois et al, 2010) we had shown that dopamine withdrawal syndrome is related to mesolimbic dopaminergic denervation and we hypothesized that a D2/D3 agonist should be beneficial on non-motor psychic symptoms that we have classified as hypodopaminergic (Ardouin et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…The present controlled study reinforces this treatment strategy with piribedil, another dopamine agonist. Although not marketed in several countries, piribedil was chosen in this study because of its broad use in France over several decades with well known safety profile and relatively low cost compared with more recent dopamine agonists, the fact that it is a non-ergot drug, its known efficacy on motor symptoms in Parkinson's disease but also based on early studies indicating a benefit on depression (Post et al, 1978;Castro-Caldas et al, 2006;Rascol et al, 2006Rascol et al, , 2010. Most importantly, in a previous study (Thobois et al, 2010) we had shown that dopamine withdrawal syndrome is related to mesolimbic dopaminergic denervation and we hypothesized that a D2/D3 agonist should be beneficial on non-motor psychic symptoms that we have classified as hypodopaminergic (Ardouin et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Dyskinesia was infrequently observed on piribedil over 1 year in patients with early PD (2.9 % of the patients) [66]. The same applied to bromocriptine (4.7 %), which was used as the active comparator in this study.…”
Section: Tolerability As Assessed In Clinical Trialsmentioning
confidence: 94%
“…Castro-Caldas and colleagues compared the effects of piribedil and bromocriptine on cognitive function in a subset of 178/428 patients with early PD assessed primarily for motor response (see above) [66]. At both 6 and 12 months, there was a significant effect of piribedil on the Wisconsin Card Sorting Test in younger (aged \ 70 years) patients, with no effect of bromocriptine [0.2 points improvement on piribedil vs. 0.3 worsening on bromocriptine (p = 0.03)].…”
Section: Non-motor Symptomsmentioning
confidence: 97%
See 2 more Smart Citations